2010
DOI: 10.1002/gcc.20788
|View full text |Cite
|
Sign up to set email alerts
|

C11orf95‐MKL2 is the resulting fusion oncogene of t(11;16)(q13;p13) in chondroid lipoma

Abstract: Chondroid lipoma, a rare benign adipose tissue tumor, may histologically resemble myxoid liposarcoma or extraskeletal myxoid chondrosarcoma, but is genetically distinct. In the current study, an identical reciprocal translocation, t(11;16)(q13;p13) was identified in three chondroid lipomas, a finding consistent with previous isolated reports. A fluorescence in situ hybridization (FISH)-based positional cloning strategy using a series of bacterial artificial chromosome (BAC) probe combinations designed to narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 28 publications
7
51
0
Order By: Relevance
“…An identical reciprocal translocation, t(11;16)(q13;p13), has been detected by cytogenetic analysis in six cases of chondroid lipoma (17)(18)(19)(20). Recurrent involvement of 11q13 has also been described in hibernoma, but not in association with 16p13 (15).…”
Section: Benign Soft Tissue Tumorsmentioning
confidence: 98%
See 2 more Smart Citations
“…An identical reciprocal translocation, t(11;16)(q13;p13), has been detected by cytogenetic analysis in six cases of chondroid lipoma (17)(18)(19)(20). Recurrent involvement of 11q13 has also been described in hibernoma, but not in association with 16p13 (15).…”
Section: Benign Soft Tissue Tumorsmentioning
confidence: 98%
“…In their study, Huang et al (20) reported that the t(11;16) (q13;p13) translocation results in a fusion of C11orf95 and MKL2. These gene rearrangements have not been identified in other soft tissue tumors thus far, and appear to be characteristic for chondroid lipoma.…”
Section: Benign Soft Tissue Tumorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have suggested a link with the reciprocal translocation t(11;16)(q13;p12-13). [4][5][6] Clinically, patients present with a painless, gradually enlarging mass, most commonly located in the proximal extremities or limb girdles. 1,2 Lesions can be located in the subcutis, superficial fascia, or intermuscular and intramuscular spaces.…”
Section: 3mentioning
confidence: 99%
“…Although less studied than BACH2, it has been identified as a serum response factor (SRF) coactivator and is therefore involved in cell growth (115)(116)(117). MKL2 fusion oncogenes have also been identified, especially in chondroid lipomas, where C11orf95-MKL2 fusions are often present (118,119).…”
Section: Integration Site: a Determining Factor In Viral Pathogenesismentioning
confidence: 99%